2009
DOI: 10.1024/0300-9831.79.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Diet Determines Features of the Metabolic Syndrome in 6- to 14-Year-Old Children

Abstract: Background/Objectives: Insulin resistance (IR) and hypertension are common in overweight children, and the adipocyte-derived hormones resistin, adiponectin, and leptin may modulate IR and blood pressure (BP). Few data exist in children on dietary determinants of IR, BP, or leptin, and no data exist on dietary determinants of resistin and adiponectin. Therefore, the objective of this study was to investigate dietary determinants of IR, BP, resistin, adiponectin, and leptin concentrations, as well as the interre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
3
21
0
1
Order By: Relevance
“…In the IDEFICS baseline survey, a low amount of physical activity was shown to be associated with a cluster of CVD risk factors including IR [13]. In accordance with the evidence from our analysis, a few other studies published data on the association of dietary factors like intake of total energy, total fat or saturated fat with IR in children and adolescents [11, 12]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the IDEFICS baseline survey, a low amount of physical activity was shown to be associated with a cluster of CVD risk factors including IR [13]. In accordance with the evidence from our analysis, a few other studies published data on the association of dietary factors like intake of total energy, total fat or saturated fat with IR in children and adolescents [11, 12]. …”
Section: Discussionsupporting
confidence: 87%
“…weight status [8], measures of central and peripheral adiposity [9, 10], dietary factors such as intake of total fat or saturated fat [11, 12], physical inactivity [13], poor physical fitness [14], low or high birth weight for gestational age [7, 15], and maternal factors like gestational diabetes [16] or unbalanced maternal nutrition [17]. Nevertheless, in children, population-based epidemiological data on the determinants of IR are still rare and mostly available from cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of fat intake has been proposed to be important in the etiology of cardiovascular diseases [29] and intake of saturated fatty acids has been found to be positively associated with insulin levels and systolic blood pressure in children [50]; however, adjusting for intake of dietary fat quality only changed the beta-coefficients slightly. Instead, the prospective associations between movement behaviours and the MetS-score became non-significant after controlling for FMI, indicating that adiposity partly explains the reported associations.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that this inflammatory index was predictive of changes in CRP levels, and that it may represent an additional indirect method of determining risk of MetS in the context of food intake [48••]. Recently, macronutrient intake (total energy, total protein, saturated fat) was found to predict features of MetS in children 6 to 14 years of age [49]. Thus, the importance of adherence to the general dietary recommendations for preventing or reducing the risk of MetS (adequate intake of omega-3 fatty acids; high intake of fruits, vegetables, grains, and nuts; and low intake of saturated fats and trans fats) must be stressed for individuals of all ages.…”
Section: Diet Inflammation and Metabolic Syndromementioning
confidence: 97%